Karakteristik Pembakaran Briket Limbah Jarak Dan Sekam Pada Berbagai Komposisi - Effendy Arief; Wahyu H. Piarah; Irwan Paserangi (Teknik Mesin "TEKNOLOGI", 2011)
The research aimed at making jatropha waste and rise husk  briquet in various  compositions, determining the combustion characteristic, briquet heating value (HHV), determining briquet chemical characteristic, and coparing it with the use of carosine stove. The research method was an experiment in the Laboratory of Mechanical Engineering, Hasanuddin University and in the Laboratory of Mining Engineering, the office of Industry, South Sulawesi Province. The result of jatropha waste briquet are in the forms of hollow cylinder in six samples. The weight of each smaple of the raw material is 1,000 grams with the concentration of 0%-50% of the mixed composition of the jatropha waste and paddy chaff waste. The result of the research reveals that the briquet with the chaff 0% composition has the highest time, temperature, and heat value. The result  of the research at the time of the real briquet burning by using the briquet stove indicates that the addition of chaff (%) composition has the impact on the decrease of the briquet burning time, and the maximal temperature obtained. The laboratory research result reveals that the addtion of chaff (%) composition has the impact on the decrease of the briquet heat value. The testing result of the chemical composition through an ultmateness analysis, the testing result of thermal characterisitic through a proximity analysis, and physical characterisitic, generally fulfily\] in the existing briquet standard (commersial briquet standard reference, import, Japan, USA).  The testing result of the comparison with the paraffing stove indicates that the use of briquet is more economical Rp.500.- than the use of the paraffin to boil 1 litre water. Keywords : briquette, rice husk, jatropha